Post-Occupancy Evaluation of Thermal Comfort Sensation of Pupils in School Establishments under Hot Arid Climate Conditions - Mansouri, Khaled; Sriti, Leila; Guedouh, Marouane Samir (Technium Social Sciences Journal, 2022)
School establishments have been considered the foundation of various civilizations, due to the importance of the educational process in producing future generations and shaping healthy societies. This paper aims to evaluate the thermal comfort sensation of pupils in school buildings under hostile climatic conditions in hot arid regions. The study employed the use of the post-occupancy approach with subjective assessments through questionnaires and physical measurements of the environmental physical parameters of thermal comfort: temperature, relative humidity, and air velocity as objective assessments. These measurements were in parallel with survey questionnaires that were undertaken during regular class sessions covering the hot and cold conditions of a school year, polling responses from 281 participants on their perception of the indoor climate. Finger's comfort indicators are calculated (PMV, predicted mean vote; and PPD, predicted percentage of dissatisfied people); and the actual people's clothing and metabolic rate are estimated in order to conclude the prevailing indoor thermal conditions. The investigations were carried out on three samples of school buildings in Biskra (Algeria) of different architectural styles. The study’s results revealed that the levels of temperature were the most crucial parameter that influenced the thermal sensation with an average of 35C° with a PMV of 2.48, and 15C° in winter with a PMV of -2.56, indicating more than 90% dissatisfaction. Therefore, a well-thought bioclimatic school design is needed to ensure acceptable indoors, and promote healthy and safe learning spaces, by adopting sustainable design principles and low-energy-consuming techniques.